Participatory construction of a sustainable tourism development model in Caibarién, Cuba - Gonzalez Herrera, Manuel Ramon (Affordable Housing Institute. Boston, Massachusetts, 2018)
The purpose of this chapter is to present the results of an analysis of problems in Caibarién resulting from the recent development of tourism in the and identifies alternatives for a sustainable development of tourism in the region. This study intends to provide a summary of useful information with the goal of improving the understanding of how the local tourism development model works and to provide guidelines for a more competitive and productive tourism system.